(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Values are those that are assimilated by the various healing processes that a person receives, which are instilled in the mind, which influence a person’s behavior. Therefore, this study of the creation of ethical values in Isan literature for sustainable social development. It has three objectives were (1) to study ethical concepts in Isan literature, (2) to explore patterns of ethical value-building in Isan literature through Isan sermons and Mor Lam performances; and 3. To analyze the value of transmission of values through Isan sermons and the practice of Mor Lam to sustainable social development.The result of study found that. The concept of creating social values based on ethics in Isan literature from several sermons or Mor Lam performances caused by the desire to cultivate the values of the people in the Isan society, reflecting Isan society from the characteristics of the Isan people, creating applied literature and entertainment, inserting morality and doctrine, instilling in the knowledge of sin, merit, goodness and punishment, knowing the duties of a person. It is a concept that wants to create human values based on goodness with themes focusing on the role of the actors, communicating through characters. There is a summary of human actions and there are criteria for judging what is good? what is evil? what are the Dos and Don’ts? It is a model that emphasizes the creation of entertainment along with the socialization of behavior. The development of values-building model through many sermons or Mor Lam demonstrations towards sustainable social development. From analyzing the data from both documents and going into the area to store insights. It shows to see the strengths, weaknesses and points that need to be developed of creating ethical values in Isan literature for sustainable social development under the conclusion of sustainable development that "Do not get lost in the old things, not drunken new things, until getting the tool called "CCDE Model" which is a component of the model to create values through the sermons or the display of Mor Lam to sustainable social development, including conservation, continuation, development and extension.